Mg-doped La0·3Sr0·7Mn0·8Mg0·2O3−δ cathode as a catalyst for NOx decomposition via H–SOFCs. Issue 3 (15th February 2020) - Li, Tingting; Qiao, Jinshuo; He, Minjie; Wang, Zhenhua; Feng, Jinsheng; Sun, Wang; Sun, Kening; Lai, Xinhua; Bai, Xiaoping; Wang, Guohua
Abstract: Proton conducting solid oxide fuel cells (H–SOFCs) with BaZr0·1 Ce0·7 Y0·2 O3-δ as electrolyte were fabricated to couple the removal of nitrogen oxides in power generation technology. Specially, a deliberately designed cathode with the composition of La0·3 Sr0·7 Mn0·8 Mg0·2 O3−δ was prepared to realize this dual function. The results indicated that the incorporation of Mg ions in La0·3 Sr0·7 MnO3−δ can improve its ability to adsorb NO and the cathode activity. At 800 °C, when using the NO as oxidant, single cell with La0·3 Sr0·7 Mn0·8 Mg0·2 O3−δ cathode was able to obtain peak power density of 48 mW cm −2 and achieve the conversion of NO to N2 more than 48%. These findings suggested that power generation coupling deNO via H–SOFC is possible and La0·3 Sr0·7 Mn0·8 Mg0·2 O3−δ was a promising cathode for this application.